Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Electrochemical preparation of luminescent graphene quantum dots from multiwalled carbon nanotubes - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemistry-A European Journal, 2012)
Green luminescent, graphene quantum dots (GQDs) with a uniform size of 3, 5, and 8.2(+/- 0.3) nm in diameter were prepared electrochemically from MWCNTs in propylene carbonate by using LiClO4 at 90?degrees C, whereas similar particles of 23(+/- 2) nm were obtained at 30?degrees C under identical conditions. Both these sets of GQDs displayed a remarkable quantum efficiency of 6.3 and 5.1?%, respectively. This method offers a novel strategy to synthesise size-tunable GQDs as evidenced by multiple characterisation techniques like transmission and scanning electron microscopy, atomic force microscopy, Raman spectroscopy and X-ray diffraction (XRD). Photoluminescence of these GQDs can be tailored by size variation through a systematic change in key process parameters, like diameter of carbon nanotube, electric field, concentration of supporting electrolyte and temperature. GQDs are promising candidates for a variety of applications, such as biomarkers, nanoelectronic devices and chemosensors due to their unique features, like high photostability, biocompatibility, nontoxicity and tunable solubility in water.
Keywords: electrochemical synthesis; graphene; Nanostructures; photoluminescence; quantum dots

In vitro enzyme mediated synthesis of metal sulfide nanoparticles: control of particle size of CdS, Ni7S6, PbS, Co3S4 nanoparticles using synthetic peptides - Ansary, Abu Ayoobul; Khan, Muhammed I.; Gaikwad, Sushama M. (Science of Advanced Materials, 2012)
We report the use of enzyme sulfite reductase for the in vitro synthesis of technologically important metal sulfide quantum dots viz. Co3S4, PbS and Ni7S6. Also we report the use of synthetic peptides to control the particle size of the above metal sulfide quantum dots in addition to CdS, synthesized using enzyme. Sulfite reductase when incubated with aqueous CdCl2, or Co(NO3)(3) or NiCl2 or Pb(NO3)(2), and Na2SO3 in the presence of the appropriate capping peptide resulted in the synthesis of particle size controlled CdS, Co3S4, Ni7S6, or PbS quantum dots respectively. These, enzyme mediated synthesized and size controlled metal sulfide quantum dots, were characterized using Absorbance and photoluminescence spectrometry, X-ray diffraction, X-ray photoelectron spectroscopy and High resolution-transmission electron microscopy.
Keywords: Capping Peptide; Enzyme; Metal Sulfide Nanoparticles; quantum dots; Size Control; Sulfite Reductase

Electrochemical resolution of multiple redox events for graphene quantum dots - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2013)
Keywords: charging energy; differential pulse voltammetry; graphene; quantum dots; single-electron transfer

Water electrolysis with a conducting carbon cloth: subthreshold hydrogen generation and superthreshold carbon quantum dot formation - Biswal, Mandakini; Deshpande, Aparna; Kelkar, Sarika; Ogale, Satishchandra (ChemSusChem, 2014)
A conducting carbon cloth, which has an interesting turbostratic microstructure and functional groups that are distinctly different from other ordered forms of carbon, such as graphite, graphene, and carbon nanotubes, was synthesized by a simple one-step pyrolysis of cellulose fabric. This turbostratic disorder and surface chemical functionalities had interesting consequences for water splitting and hydrogen generation when such a cloth was used as an electrode in the alkaline electrolysis process. Importantly, this work also gives a new twist to carbon-assisted electrolysis. During electrolysis, the active sites in the carbon cloth allow slow oxidation of its surface to transform the surface groups from COH to COOH and so forth at a voltage as low as 0.2V in a two-electrode system, along with platinum as the cathode, instead of 1.23V (plus overpotential), which is required for platinum, steel, or even graphite anodes. The quantity of subthreshold hydrogen evolved was 24mLcm(-2)h(-1) at 1V. Interestingly, at a superthreshold potential (>1.23V+overpotential), another remarkable phenomenon was found. At such voltages, along with the high rate and quantity of hydrogen evolution, rapid exfoliation of the tiny nanoscale (5-7nm) units of carbon quantum dots (CQDs) are found in copious amounts due to an enhanced oxidation rate. These CQDs show bright-blue fluorescence under UV light.
Keywords: Carbon; electrolysis; Hydrogen; photoluminescence; quantum dots

Hybrid perovskite quantum nanostructures synthesized by electrospray antisolvent-solvent extraction and intercalation - Naphade, Rounak; Nagane, Satyawan; Shanker, G. Shiva; Fernandes, Rohan; Kothari, Dushyant; Zhou, Yuanyuan; Padture, Nitin P.; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2016)
Perovskites based on organometal lead halides have attracted great deal of scientific attention recently in the context of solar cells and optoelectronic devices due to their unique and tunable electronic and optical properties. Herein, we show that the use of electrospray technique in conjunction with the antisolventsolvent extraction leads to novel low-dimensional quantum structures (especially 2-D nanosheets) of CH3NH3PbI3- and CH3NH3PbBr3-based layered perovskites with unusual luminescence properties. We also show that the optical bandgaps and emission characteristics of these colloidal nanomaterials can be tuned over a broad range of visible spectral region by compositional tailoring of mixed-halide (I- and Br-based) perovskites.
Keywords: 2D nanostructure systems; antisolvent-solvent extraction; bandgap tuning; electrospray; nanosheets; perovskite; quantum dots

Nanoporous graphene enriched with Fe/Co-N active sites as a promising oxygen reduction electrocatalyst for anion exchange membrane fuel cells - Palaniselvam, Thangavelu; Kashyap, Varchaswal; Bhange, Siddeswar N.; Baek, Jong-Beom; Kurungot, Sreekumar (Advanced Functional Materials, 2016)
Here, a simple but efficient way is demonstrated for the preparation of nanoporous graphene enriched with Fe/Co-nitrogen-doped active sites (Fe/Co-NpGr) as a potential electrocatalyst for the electrochemical oxygen reduction reaction (ORR) applications. Once graphene is converted into porous graphene (pGr) by a controlled oxidative etching process, pGr can be converted into a potential electrocatalyst for ORR by utilizing the created edge sites of pGr for doping nitrogen and subsequently to utilize the doped nitrogens to build Fe/Co coordinated centers (Fe/Co-NpGr). The structural information elucidated using both XPS and TOF-SIMS study indicates the presence of coordination of the M-N (M = Fe and Co)-doped carbon active sites. Creation of this bimetallic coordination assisted by the nitrogen locked at the pore openings is found to be helping the system to substantially reduce the overpotential for ORR. A 30 mV difference in the overpotential () with respect to the standard Pt/C catalyst and high retention in half wave potential after 10 000 cycles in ORR can be attained. A single cell of an anion exchange membrane fuel cell (AEMFC) by using Fe/Co-NpGr as the cathode delivers a maximum power density of approximate to 35 mWcm(-2) compared to 60 mWcm(-2) displayed by the Pt-based system.
Keywords: electrocatalyst; nitrogen doping; oxygen reduction reaction; porous grapheme; quantum dots

CdSe quantum dot-based nanocomposites for ultralow-power memristors - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Shankar, Uday; Rath, Arup Kumar; Sahu, Satyajit (ACS Applied Nano Materials, 2022)
The explosion in digital communication with the huge amount of data and the internet of things (IoT) led to the increasing demand for data storage technology with faster operation speed, high-density stacking, nonvolatility, and low power consumption for saving energy. Metal chalcogenide-based quantum dots (QDs) show excellent nonvolatile resistive memory behavior owing to their tunable electronic states and control in trap states by passivating the surface with different ligands. Here, we synthesized high-quality colloidal monodispersed CdSe QDs by the hot injection method. The CdSe QDs were blended with an organic polymer, poly(4-vinylpyridine) (PVP), to fabricate an Al\textbackslashCdSe-PVP\textbackslashAl device. Our device shows excellent bipolar nonvolatile resistive random access memory (RRAM) switching behavior with a high current ON/OFF ratio (I-ON/OFF) of 6.1 x 10(4), and it consumes ultralow power. The charge trapping and detrapping in the potential well formed by the CdSe QD and PVP combination result in resistive switching. This CdSe-PVP-based resistive random access memory (RRAM) device with a high I-ON/OFF, ultrafast switching speed, high endurance, low operating voltage, and long retention period can be used as a high-performance and ultralow-power memristive device.
Keywords: memory switching; memristor; metal chalcogenides; nonvolatile; quantum dots

Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization

Multi-bandgap quantum dots ensemble for near-infrared photovoltaics - Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Rath, Arup K. (Energy Technology, 2023)
Narrow bandgap quantum dots (QDs) are an important class of materials for near-infrared (NIR) optoelectronic devices owing to their size-tunable bandgap and chemical root processing. In photovoltaic applications, NIR QDs could be particularly useful to complement the sub-bandgap transmission loss of NIR solar radiation from perovskite and c-Si solar cells. However, insufficient carrier extraction thickness associated with the narrow NIR excitonic bandwidth of QDs limits the conversion efficacy of the broad NIR solar spectrum. Here, we utilize a multi-bandgap QD ensemble which widens the NIR absorption bandwidth to mimic the broad solar spectrum. A solution-phase ligand passivation strategy is used to control doping properties and energy level alignment of multi-bandgap QDs. We successfully developed bulk-heterojunction solar cells using the multi-bandgap QD ensemble, which yields higher carrier extraction thickness and broader NIR absorption. The gain from NIR absorption and carrier transport resulted in higher short-circuit current generation and power conversion efficiency (PCE) in solar cell devices. The champion device shows 8.73% PCE under 1.5 AM solar illumination and 7.44% and 5.05% PCE for the NIR photons transmitted from perovskite and c-Si layers.
Keywords: bulk-heterojunctions; multi-bandgap; near-infrared; quantum dots; solar cells; surface passivation

One-pot, easy and scalable synthesis of large-size short wave length IR emitting PbS quantum dots - Sahu, Umasharan; Prasad, Bhagavatula L. V. (Photochemistry and Photobiology, 2024)
This study presents a versatile and efficient method to synthesize large-size lead sulfide (PbS) quantum dots (QDs) that display emission in the short-wave infrared (SWIR) region, using accessible and stable diethylammonium diethyldithiocarbamate (C-2)(2)DTCA and octylammonium octyldithiocarbamate (C(8)DTCA) as sulfur sources. As these sulfur sources enable the formation of well-dispersed, large-size PbS QDs in a very convenient way, this method can further be taken up for scale-up studies. Importantly, this approach allows precise control over QD sizes, thereby enhancing their SWIR optical properties. By adjusting the hot injection temperatures and sulfur source concentrations, different synthesis routes are explored, providing flexibility for the desired QD characteristics. The results presented here offer a promising opportunity to leverage the synthesized PbS QDs in applications such as optoelectronics, sensors, and imaging technology.
Keywords: hot injection method; Optical properties; quantum dots; short wave IR emission

Photocatalytic regeneration of reactive cofactors with inP quantum dots for the continuous chemical synthesis - Chakraborty, Indra Narayan; Jain, Vanshika; Roy, Pradyut; Kumar, Pawan; Vinod, Chathakudath P.; Pillai, Pramod P. (ACS Catalysis, 2024)
The shuttling of redox-active nicotinamide cofactors between the light and dark cycles is the key to the continuous production of biomass in photosynthesis. The replication of such processes in artificial photosynthetic systems demands fast photoregeneration as well as simultaneous integration of these nicotinamide cofactors into the dark cycle. Here, we report the design of an artificial photosynthetic system for the continuous production of butanol via the constant photoregeneration and consumption of nicotinamide cofactors, powered by an indium phosphide quantum dot (InP QD) photocatalyst and alcohol dehydrogenase (ADH) enzyme, respectively. A strong electrostatic attraction between the oppositely charged InP QDs and electron mediators significantly enhanced the charge extraction and utilization processes, enabling a fast (similar to 30 min, with a turn over frequency of similar to 1333 h(-1)), quantitative (>99%), and selective photoregeneration of enzymatically active nicotinamide cofactors in the light cycle. These photoregenerated nicotinamide cofactors were further coupled in the dark cycle to trigger the ADH oxidoreductase enzyme for the production of butanol, via sequential as well as simultaneous light-dark cycles. The amount of butanol produced under simultaneous light-dark cycles was higher than the stoichiometric limit, proving the constant regeneration and consumption of nicotinamide cofactors in light and dark cycles, respectively. Thus, a proper design and integration of the InP QD-based photocatalytic cycle with the enzymatic cycle led to the effective electron shuttling between light and dark cycles, as seen in photosynthesis.
Keywords: artificial photosynthesis; biologicalcofactors; charge transfer; indiumphosphide; Photocatalysis; quantum dots

Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS

Synthesis and processing strategy for high-bandgap PbS quantum dots: a promising candidate for harvesting high-energy photons in solar cells - Shinde, Dipak Dattatray; Sharma, Anjali; Dambhare, Neha V.; Mahajan, Chandan; Biswas, Arindam; Mitra, Anurag; Rath, Arup K. (ACS Applied Materials & Interfaces, 2024)
The wide tunability of the energy bandgap of colloidal lead sulfide (PbS) quantum dots (QDs) has uniquely positioned them for the development of single junction and tandem solar cells. While there have been substantial advancements in moderate and narrow bandgap PbS QDs-ideal for single junction solar cells and the bottom cell in tandem solar cells, respectively; progress has been limited in high-bandgap PbS QDs that are ideally suited for the formation of the top cell in tandem solar cells. The development of appropriate high bandgap PbS QDs would be a major advancement toward realizing efficient all-QD tandem solar cells utilizing different sizes of PbS QDs. Here, we report a comprehensive approach encompassing synthetic strategy, ligand engineering, and hole transport layer (HTL) modification to implement high-bandgap PbS QDs into solar cell devices. We achieved a greater degree of size homogeneity in high-bandgap PbS QDs through the use of a growth retarding agent and a partial passivation strategy. By adjusting the ligand polarity, we successfully grow HTL over the QD film to fabricate solar cells. With the aid of an interface modifying layer, we incorporated an organic HTL for the realization of high-performance solar cells. These solar cells exhibited an impressive open-circuit voltage of 0.824 V and a power conversion efficiency of 10.7%, marking a 360% improvement over previous results.
Keywords: charge transport; lead sulfide; ligand passivation; quantum dots; solar cell

Synergistic improvement of narrow bandgap PbS quantum dot solar cells through surface ligand engineering, near-infrared spectral matching, and enhanced electrode transparency - Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2025)
The tunability of the energy bandgap in the near-infrared (NIR) range uniquely positions colloidal lead sulfide (PbS) quantum dots (QDs) as a versatile material to enhance the performance of existing perovskite and silicon solar cells in tandem architectures. The desired narrow bandgap (NBG) PbS QDs exhibit polar (111) and nonpolar (100) terminal facets, making effective surface passivation through ligand engineering highly challenging. Despite recent breakthroughs in surface ligand engineering, NBG PbS QDs suffer from uncontrolled agglomeration in solid films, leading to increased energy disorder and trap formation. The limited NIR transparency of commonly used indium-doped tin oxide (ITO) electrodes and inadequate NIR radiation from commercially available solar simulators further compromise the true performance of NBG PbS QDs in solar cells. Here, we employ a hybrid ligand strategy based on inorganic cadmium halide and organic thiol molecules, leading to the partial substitution of surface Pb atoms with Cd heteroatoms. This hybrid ligand strategy substantially reduces undesired QD fusion in solid films, improving the photophysical and electronic properties. By modulating the thickness of the ITO layer and managing refraction loss through a ZnO layer coating, we improved NIR transparency to above 80%. We combine an NIR light source with a solar simulator to achieve near-ideal spectral matching for a broader range with standard AM1.5G illumination. Enhancements in surface passivation of QDs, improvements in NIR transparency of electrodes, and a spectral matched light source setup help us achieve solar cell power conversion efficiencies of 12.4%, 4.48%, and 1.37% under AM 1.5G, perovskite filter, and silicon filter illuminations, respectively. A record open-circuit voltage (V oc) of 0.54 V and short-circuit current density (J sc) of 38.5 mA/cm2 are achieved under AM 1.5G illumination. We attribute these advancements in photovoltaic parameters to the reduction in Urbach tail states and intermediate trap density originating from superior surface passivation of QDs.
Keywords: lead sulfide; ligand passivation; near-infrared; quantum dots; solar cell; tandem solarcell

Self-powered photodetection in AgBiS2 nanocrystals synthesized from AgBi-mixed-metal thiolate - Das, Mouli; Swathi, S. P.; Prasad, Bhagavatula L. V. (ACS Applied Nano Materials, 2026)
AgBiS2 has emerged as a promising optoelectronic material owing to its high absorption coefficient, environmentally friendly and abundant components, offering a sustainable alternative to lead- and cadmium-based chalcogenides. Realizing the full potential of AgBiS2 devices, however, requires scalable synthesis routes that include development of suitable precursors and minimize the use of harsh solvents, elevated temperatures, inert environments, etc. Here, we present a facile, solvent-free synthesis of phase pure AgBiS2 nanocrystals (NCs) at room temperature and under ambient conditions, enabled by the AgBi mixed-metal thiolate (AgBi-MMT) precursor complex. The initial choice of metal salts determines the nature of the metal thiolate intermediate complex, which subsequently influences the quality of the resulting AgBiS2 NCs. As a single-source precursor of the metals, AgBi-MMT enables controlled release of Ag+ and Bi3+ ions, yielding phase-pure AgBiS2 NCs. Furthermore, the MMT that is derived from AgI and BiI3 precursors promotes in situ surface passivation of the AgBiS2 NCs by iodide ions by trapping molecular I2 within its matrix. Under illumination, these iodide ions undergo reversible migration, generating a built-in potential and enabling self-powered photodetection in devices prepared from the as-synthesized NCs. This work expands the synthesis methodology of AgBiS2, highlighting the importance of metal thiolates as precursors in nanomaterial syntheses, and influence of iodine species in photo-operational devices.
Keywords: built-in potential; iodine; ion migration; layered; quantum dots